Diagnostic challenges of gliosarcoma: case report of a rare glioblastoma histopathological variant - Karasev, Sergey; Talybov, Rustam; Chertoyev, Shamil; Trofimova, Tatyana; Mochalov, Vadim; Kleshchevnikova, Tatyana; Loginova, Natalya; Karaseva, Irina (Frontiers in Radiology, 2025)
BackgroundAccording to the 5th revision of World Health Organization (WHO) of central nervous system tumors classification, gliosarcoma is a malignant tumor grade 4 and is the rarest and aggressive subtype of isocitrate dehydrogenase (IDH) wild-type glioblastoma. The special histopathological feature of the tumor is its biphasic differentiation including both the glial and the sarcomatous (mesenchymal) components of the tumor. The characteristics mentioned above create difficulties in radiological and histological diagnoses. Because of its rarity, gliosarcoma is typically not even considered in the differential diagnosis.Case presentationThis clinical case study describes a 55-year-old man exhibiting acute right-sided hemiparesis and disorientation for 12 h with loss of consciousness. A brain МRI of the patient revealed an intracerebral mass in the left frontoparietal area with close relationship with the dura mater, ring-like enhancement, severe perifocal edema, restricted diffusion of the solid component, internal vascular shunts, microhemorrhages, and elevated perfusion values. At the preoperative stage, the differential diagnosis included glioblastoma, solitary metastasis, and the possibility of an anaplastic meningioma. Tumor microsurgical resection was performed. According to the results of histological and immunohistochemical studies, gliosarcoma was diagnosed.DiscussionThe only characteristic gliosarcoma feature was the phenomenon of solid node heterogeneity detected on the conventional T2-weighted sequence: a combination of hypo- and hyperintense parts. While multiparametric magnetic resonance imaging (MRI) aids in differentiating high-grade gliomas, metastases, and meningiomas, gliosarcoma remains underrecognized because of overlapping features. The observed T2 heterogeneity may serve as a potential radiological marker for gliosarcoma. Accurate and timely identification of brain tumor type is required to establish the appropriate extent of resection in surgical planning.ConclusionThis case publication does not intend to ignore the data of conventional sequences and instead considers them to be included in the structure of the multiparametric MRI protocol. However, larger studies are needed to validate the findings of this case study and refine diagnostic criteria for this rare tumor.